Parental education and guided self-management of asthma and wheezing in the pre-school child: a randomised controlled trial. - Stevens, C; Wesseldine, L; Couriel, J; Dyer, A; Osman, L; Silverman, M (2002)
BACKGROUND: The effects on morbidity were examined of providing an educational intervention and a written guided self-management plan to the parents of pre-school children following a recent attendance at hospital for asthma or wheeze. METHODS: A prospective, randomised, partially blinded, controlled trial was designed at two secondary care centres. Over a 13 month period 200 children aged 18 months to 5 years at the time of admission to a children's ward or attendance at an accident and emergency department or children's (emergency) assessment unit (AandE/CAU) with a primary diagnosis of acute severe asthma or wheezing were recruited. 101 children were randomised into the control group and received usual care and 99 were assigned to the intervention group and received: (1) a pre-school asthma booklet; (2) a written guided self-management plan; and (3) two 20 minute structured educational sessions between a specialist respiratory nurse and the parent(s) and child. Subjects were assessed at 3, 6, and 12 months. The main outcomes were GP consultation rates, hospital re-admissions, and attendances at AandE/CAU. Secondary outcomes included disability score, caregivers' quality of life, and parental knowledge of asthma. RESULTS: There were no statistically significant differences between the two groups during the 12 month follow up period for any of the main or secondary outcome measures. CONCLUSIONS: These results do not support the hypothesis that the introduction of an educational package and a written guided self-management plan to the parents of pre-school children with asthma who had recently attended hospital for troublesome asthma or wheeze reduces morbidity over the subsequent 12 months.